(untitled) (GYMNASIUM, 2017)
The paper presents the influence of physical training level on the sports performances of junior female gymnasts aged 12-15. This scientific approach has led to the organization of an experimental study within the female junior Olympic team, carried out in the period September 2012 – February 2013, on a group of 14 female gymnasts. Seven control tests were applied to the experimental group and they concerned the development of force/speed, of force and of specific endurance. The analysis of physical training level specific to junior female gymnasts aged 12-15 underlines the improvement of the explosive force of lower limbs, of arm muscle force, of lumbar muscles, of special endurance and of the sense of balance. The analysis of physical training level specific to junior female gymnasts aged 12-15 in accordance with the sports performances obtained in competitions has shown insignificant differences between them and the need to improve the level of technical training by introducing didactic programs within the sports training.